1995
DOI: 10.1007/bf00262197
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-gold localization of hepatotoxins in cyanobacterial cells

Abstract: A polyclonal antibody against the potent hepatotoxic cyclic peptide microcystins and nodularins was used in conjunction with immuno-gold labelling to localize the toxins in three strains of cyanobacteria. Ultrastructurally, there were no major differences between unicellular Microcystis aeruginosa strain PCC 7820 (toxin-producing strain) and M. aeruginosa strain UTEX 2063 (non-toxin-producing strain), except that M. aeruginosa PCC 7820 cells had a sheath. The thickness of the sheath was about 12 nm and was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 24 publications
5
54
1
3
Order By: Relevance
“…On the other hand, low concentration of NP (0.05-0.2 mg/L) stimulated slightly to the synthesis of chlorophyll a and carotinoid of toxic strain PCC7820. Shi et al (1995) found that microcystin was associated with the thylakoid membranes of M. aeruginosa PCC7820, suggesting a close physiological association between microcystins and the photosynthetic machinery of the cell. The finding in our study may suggest that NP had taken part in the physiological activity of some toxic M. aeruginosa cells and such activity had a certain extent relationship with toxin production.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, low concentration of NP (0.05-0.2 mg/L) stimulated slightly to the synthesis of chlorophyll a and carotinoid of toxic strain PCC7820. Shi et al (1995) found that microcystin was associated with the thylakoid membranes of M. aeruginosa PCC7820, suggesting a close physiological association between microcystins and the photosynthetic machinery of the cell. The finding in our study may suggest that NP had taken part in the physiological activity of some toxic M. aeruginosa cells and such activity had a certain extent relationship with toxin production.…”
Section: Discussionmentioning
confidence: 91%
“…The reason is not clear. The observation by Shi et al (1995) of some localization of microcystin in the cell wall and sheath suggest that microcystin may act as transmembrane transporters of calcium, magnesium or other metals. Stimulation of membrane receptors is believed to be a cause for the activation of cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent MC-localization studies have used cryosectioning to prepare cells for immunogold labelling and electron microscopy since this technique avoids using organic solvents, which extract MC from cells . Shi et al (1995) and Young et al (2005) found that most of the intracellular pool of MCs in Microcystis, as determined by immunogold label, is localized in the thylakoid region, possibly indicating a role for MCs in the assembly, structure or function of the photosynthetic apparatus, or in other light-related processes. High labelling densities were also found around polyphosphate bodies .…”
Section: Introductionmentioning
confidence: 99%
“…Antisera raised against MC-LR have been successfully used in immunoelectron microscopy to localize MCs in laboratory cultures of Microcystis spp. (Shi et al, 1995;Young et al, 2005;Gerbersdorf, 2006). Traditional preparative methods for immunoelectron microscopy (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation